Chemical-Enhanced Oil Recovery Using N,N-Dimethylcyclohexylamine on a Colombian Crude Oil - Diego R. Merchan-Arenas; Cindy Carolina Villabona-Delgado (International Journal of Chemical Engineering)
Oil recovery was improved using the tertiary amine, N,N-dimethylcyclohexylamine (DMCHA), a powerful and promissory switchable solvent, in simulated conditions similar to the Colombian crude oil reserves. Firstly, the Colombian crude oil (CCO) and the soil were characterized completely. Afterwards, an aged crude-rock system was obtained to use DMCHA that gave an oil crude extraction of 80% in our preliminary studies. Thus, a sand-pack column (soil-kaolin, 95 : 5) frame saturated with CCO was used to simulate the conditions, in which DMCHA could recover the oil. After the secondary recovery process, 15.4–33.8% of original oil in place (OOIP) is obtained. Following the injection of DMCHA, the recovery yield rose to 87–97% of OOIP. Finally, 54–60% of DMCHA was recovered and reinjected without affecting its potential in the simulated conditions.